Economic incentives can enhance policy efforts to improve water quality in Asia - Balasubramanya, Soumya; Wichelns, Dennis (Informa UK Limited, 2012)
This article describes the conceptual advantages of including economic incentives in the basket of policy alternatives available for motivating improvements in water quality. With a particular focus on Asia, we discuss the incentives available for encouraging reductions in point and nonpoint source pollutants in urban, rural, and peri-urban settings. Several countries in Asia are implementing some form of economic incentives, either directly, in the form of effluent taxes or subsidies, or in combination with regulatory measures that help to ensure water quality standards are achieved. We also describe the importance of institutional capacity and political will in support of economic incentives, and the increasing usefulness of incentive programmes as economies develop and expand. The discussion includes several examples of programmes in China and Thailand, along with observations from India, Japan, Korea, and the Philippines.